Our mother, our paradise - Abd Razak, Dzulkifli (2007)
MY mother passed away exactly a year ago last week after being hospitalised for several months at Kuala Lumpur Hospital. She had been hospitalised elsewhere but had not experienced anything comparable to the care she received under Datuk Dr Zaki Morad and his dedicated staff. It was because of this that the departure of my mother was made a little easier, knowing full well that we had tried everything we could to provide the best for her and that it was time for her to return to God. As believers, we are convinced that there can never be a better place to return to, except to our beloved Creator.